Chiral recognition and determination of enantiomeric excess of chiral compounds by UV-visible-shortwave near infrared diffuse reflectance spectroscopy with chemometrics. Issue 22 (28th February 2017) - Lu, Xiaomei; Tang, Jie; Dang, Xinxin; Jing, Xiaoli; Xu, Kailin; Li, Hui; Liang, Bing
Abstract : UV-vis-SWNIR DRS with chemometrics is applied to chiral recognition and determination of e.e values of tartaric acid for the first time. Abstract : A simple approach is proposed for the chiral recognition and determination of enantiomeric excess of enantiomers, based on a UV-visible-shortwave near infrared diffuse reflectance spectroscopy (UV-vis-SWNIR DRS) technique combined with chemometrics. The results of chiral recognition show that principal component analysis (PCA) combined with UV-vis-SWNIR DRS is able to discriminate chiral compounds based on different chirality. Determination of enantiomeric excess value was performed by linear regression model partial least squares (PLSR) and non-linear regression model support vector machine regression (SVR) combined with UV-vis-SWNIR diffuse reflectance spectroscopy. After wavelength selection, spectral pre-treatments and parameter optimization, both models showed good prediction ability: the determination coefficients ( R 2 ) of prediction set by the PLSR model and the SVR model are 0.9921 and 0.9951, respectively, and mean standard errors (MSEs) are 0.0029 and 0.0020, respectively. The SVR model has a better prediction effect. The detection limit (LD) of this method was 0.059. The results prove that this approach can be used to discriminate chiral compounds and determine enantiomeric excess of enantiomers.